Pengaruh Dana Desa Dan Apbdesa Terhadap Kesejahteraan Masyarakat (Studi Kasus Desa Pandansari Kabupaten Lumajang) - Zainul Zainul; Budi Wahono; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The aims of this study are: 1) To find out how the effect of the use of village funds for improving the welfare of the Pandansari village community in Lumajang Regency, 2) To find out how the Village Revenue and Expenditure Budget effect on improving the welfare of the Pandansari village community in Lumajang Regency. By using a non-probability sampling technique, the results of the study indicate that the utilization of the Village Fund and Village Revenue and Expenditure Budget has a significant positive effect on Community Welfare. This study also indicates that the use of Village Funds and Village Revenue and Expenditure Budget can improve Community Welfare. Keywords: Village Fund, Village Revenue and Expenditure Budget